PENGARUH PENGGUNAAN MEDIA RODA BILANGAN TERHADAP KEMAMPUAN PENJUMLAHAN SISWA KELAS 1 MI AT-TAQWA PANAIKANG - Mahyuni, Ani; Mulawakkan Firdaus, Andi; Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of number wheel media on the addition skillsof first-grade students at MI At-Taqwa Panaikang. The research problem formulationin this study is whether there is an effect of using number wheel media on theaddition skills of first-grade students at MI At-Taqwa Panaikang. This study used aquantitative approach with the Pre-Experimental Design method and One GroupPretest-Posttest design. The population in the study were all first-grade students atMI At-Taqwa Panaikang, with a sample of 22 students, with a saturated (full)sampling technique. Data collection techniques were carried out through learningachievement tests given before treatment (pretest) and after treatment (posttest).The research instruments were learning achievement tests (pretest and posttest)and student activity observation sheets. Data analysis techniques used descriptiveand inferential statistics with the help of SPSS 31. Data normality tests wereconducted using the Shapiro-Wilk test, which showed that the pretest and posttestdata were normally distributed. Hypothesis testing used was the paired sample ttest. The results of the study showed an increase in the average score from 41.27(Pretest) to 88.14 (Posttest). The paired sample t-test showed a significance valueof 0.001 <0.05, which means H0 is rejected and H1 is accepted. Thus, it can beconcluded that the use of number wheel media has a significant effect on studentlearning outcomes in addition skills in grade 1 of MI At-Taqwa Panaikang.